2006
DOI: 10.1300/j081v19n03_08
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Visibility of Outdoor and Indoor Physical Activity Features and Participation in Physical Activity Among Older Adults in Retirement Communities

Abstract: In this paper we examine how the presence and visibility of outdoor and indoor physical activity resources (e.g., walking path/ trail, outdoor tennis courts, gardens, etc.) influences participation in physical activity among elderly residents in non-profit continuing care retirement communities and other senior housing communities. This paAnjali Joseph, PhD, is per reports findings from a survey of 800 such communities. A social ecological model was used to study the relationships between the environment and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 14 publications
3
48
2
Order By: Relevance
“…Few village characteristics were significantly associated with PA. We found the presence of recreational facilities within the village was unrelated to PA in our sample. This contrasted with findings by Joseph et al [25], though in some ways, our finding was unsurprising given that walking was the most popular PA mode participants engaged in. Moreover, the PA types that would occur in the recreational facilities provided (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Few village characteristics were significantly associated with PA. We found the presence of recreational facilities within the village was unrelated to PA in our sample. This contrasted with findings by Joseph et al [25], though in some ways, our finding was unsurprising given that walking was the most popular PA mode participants engaged in. Moreover, the PA types that would occur in the recreational facilities provided (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Both the leaders and staff reported having garden interests and skills and stated that going outdoors facilitated restorative breaks during the busy workdays, all of which might motivate the leaders and staff to bring the residents outdoors. Facilitating and acknowledging that going outdoors is a part of clinical practice for the elderly is underpinned by reported findings related to improved physical benefits (Jacobs et al, 2008;Joseph et al, 2005;Sugiyama & Thompson, 2005), cognitive benefits (Plassman, Williams, Burke, Holsinger, & Benjamin, 2010;Spector et al, 2003;Woods, Aguirre, Spector, & Orrell, 2012) and behavioral improvements (Woodhead, Zarit, Braungart, Rovine, & Femia, 2005). Similarly, continuous activity programming has been reported to reduce staffing needs, increase the time involved in activities, decrease the use of psychotropic medication, improve nutrition and increase family satisfaction (Volicer, Simard, Pupa, Medrek, & Riordan, 2006).…”
Section: General Clinical Usementioning
confidence: 99%
“…Several authors have reported that nature seems to be beneficial for patients suffering from dementia (Lovering, Cott, Wells, Taylor, and Wells, 2002;Ottosson & Grahn, 2005), with observing nature and plants, and experiencing fresh air as important experiences (Kearney & Winterbottom 2005). Joseph, Zimring, Kojetin, and Kiefer (2005) reported that the number of residents in retirement communities participating in physical activities depended on the attractiveness of both the indoor and outdoor environments. Easy access to outdoor environments has been emphasised (Mooney & Nicell, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A few additional studies have examined whether certain built or structural characteristics influence physical activity among elementary students, 18 older adults, 19 and preschoolers, 20 finding that more facilities and equipment and opportunities (e.g., classes) translated into increased activity levels.…”
Section: Introductionmentioning
confidence: 99%